The power of geohistorical boundaries for modeling the genetic background of human populations: The case of the rural catalan Pyrenees - Fibla, Joan; Maceda, Iago; Laplana, Marina; Guerrero, Montserrat; Álvarez, Miguel Martín; Burgueño, Jesús; Camps, Agustí; Fàbrega, Jordi; Felisart, Josefina; Grané, Joan; Remón, José Luis; Serra, Jordi; et al. (Frontiers in Genetics, 2023)
The genetic variation of the European population at a macro-geographic scale follows genetic gradients which reflect main migration events. However, less is known about factors affecting mating choices at a micro-geographic scale. In this study we have analyzed 726,718 autosomal single nucleotide variants in 435 individuals from the Catalan Pyrenees covering around 200 km of a vast and abrupt region in the north of the Iberian Peninsula, for which we have information about the geographic origin of all grand-parents and parents. At a macro-geographic scale, our analyses recapitulate the genetic gradient observed in Spain. However, we also identified the presence of micro-population substructure among the sampled individuals. Such micro-population substructure does not correlate with geographic barriers such as the expected by the orography of the considered region, but by the bishoprics present in the covered geographic area. These results support that, on top of main human migrations, long ongoing socio-cultural factors have also shaped the genetic diversity observed at rural populations.